The Authority of The Indonesian Navy In Conducting Investigations of Criminal Acts of Narcotics Through The Indonesian Sea - M.Iqbal (Faculty of Law, Merdeka University Surabaya, 2021)
In its main task, the Indonesian Navy has duties, one which is to carry out law enforcement at sea. Indonesia's position is in the cross position of the world and is used as the Sea Lines of Communication (SLOC) and Sea Lines of Oil Trade (SLOT), as well as being one of the most strategic regions in the Asia Pacific region as the center of economic growth (Center for Economic Growth). The vast area of ​​the Indonesian sea makes it vulnerable to criminal acts in the Indonesian sea area. On this basis, the authors conducted a study with the aim of analyzing the investigative authority of the Indonesian Navy against narcotics crimes based on legal principles in and through the Indonesian sea. The results showed that the Navy has the authority to investigate at sea, but for narcotics cases it has not been given the authority. The right form of law as the basis for the use of a forum for regulating the authority of the Indonesian Navy in the matter of narcotics smuggling by foreign-flagged ships in Indonesian seas, namely the Government immediately amending Law Number 5 of 1983 concerning Indonesia's EEZ by adding the authority of the Indonesian Navy as investigators without reducing its authority owned by the National Police or the National Narcotics Agency in the investigation of narcotics smuggling